MOTIVATION PRACTICES AMONG EMPLOYEES IN THE TOURISM INDUSTRY IN KOTTAYAM DISTRICT, KERALA: AN EMPIRICAL STUDY - Nair, Sreejith; B., Selvaveera Kumar; S., Dhinesh Babu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the motivational practices within the tourism industry of Kottayam District, Kerala, focusing on their efficacy and impact on employee satisfaction and productivity. The dynamic nature of the tourism sector, characterized by irregular hours and seasonal fluctuations, underscores the critical role of effective motivational strategies in enhancing employee performance and ensuring high levels of customer satisfaction. Primary data collected from 110 employees through a structured questionnaire, along with secondary sources, provides a comprehensive understanding of the workforce's demographic characteristics and their motivational preferences. The findings reveal that financial incentives and work-life balance are the most influential motivators, as indicated by the highest mean scores among the factors analysed. Other motivational practices such as recognition, career development opportunities, empowerment, and a positive work environment also contribute significantly, albeit to a lesser extent, suggesting a need for a multifaceted approach to employee motivation. By aligning motivational strategies with the diverse needs and expectations of the workforce, employers in the tourism industry can foster a more motivated, productive, and committed workforce, ultimately driving the sector’s growth and success in the region.